The Effect of Using Student Worksheets with A STEM Approach on Vibrations, Waves, and Sound Material on Learning Outcomes of Class VIII Students - Ramlan Silaban; Shinta Rap Sitinjak (CV. ULIL ALBAB CORP, 2024)
This research aims to determine the effect of using STEM-based student worksheets on Vibrations, Waves and Sound material on learning outcomes of class VIII students. This research was quasi-experimental with a pretest-posttest control group design. This research was carried out from March to April at SMP N 3 Harian. This research uses a test instrument in the form of 20 multiple-choice questions and a non-test in form of a student response questionnaire to STEM-based student worksheets of 15 statements. The sampling technique used in this research was random sampling consisting of 60 students, namely 30 students in class VIII B as experimental class and 30 students in class VIII A as a control class. Hypothesis testing uses the t-test with research results tcount > ttable. Based on the research result, it can be concluded that there is an influence on learning outcomes using student worksheets with a STEM approach on vibrations, waves, and Sound material in class VIII.